Expression Profiling of Castanea Genes during Resistant and Susceptible Interactions with the Oomycete Pathogen Phytophthora cinnamomi Reveal Possible Mechanisms of Immunity - Santos, Carmen; Duarte, Sofia; Tedesco, Sara; Fevereiro, Pedro; Costa, Rita L. (Frontiers in Plant Science, 2017)
The most dangerous pathogen affecting the production of chestnuts is Phytophthora cinnamomi a hemibiotrophic that causes root rot, also known as ink disease. Little information has been acquired in chestnut on the molecular defence strategies against this pathogen. The expression of eight candidate genes potentially involved in the defense to P. cinnamomi was quantified by digital PCR in Castanea genotypes showing different susceptibility to the pathogen. Seven of the eight candidate genes displayed differentially expressed levels depending on genotype and time-point after inoculation. Cast_Gnk2-like revealed to be the most expressed gene across all experiments and the one that best discriminates between susceptible and resistant genotypes. Our data suggest that the pre-formed defenses are crucial for the resistance of C. crenata to P. cinnamomi. A lower and delayed expression of the eight studied genes was found in the susceptible Castanea sativa, which may be related with the establishment and spread of the disease in this species. A working model integrating the obtained results is presented.